Transforming Learning in Islamic Education: A Study of Pedagogical Change and Student Achievement in Indonesia - Fahrurrozi, Fahrurrozi; Qomar, Mujamil; Sokip, Sokip; Abdulghani, Naser Ali (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study explores transformative pedagogical innovations implemented at SMAS Al-Ma’arif NU Al-Manshuriyah Bonder, a faith-based senior high school in Central Lombok, Indonesia. Aiming to improve student learning outcomes and academic performance, the research adopts a qualitative case study approach. Data were gathered through in-depth interviews with teachers and students, classroom observations, and document analysis of instructional strategies. The findings highlight several key innovations, including the integration of digital technology in teaching, proactive dissemination of student competition opportunities, and the evolving role of teachers as academic mentors. These practices reflect a dynamic shift in instructional culture, emphasizing collaboration, motivation, and student-centered learning. The study underscores the importance of sustained institutional support and teacher development to ensure the long-term success of such innovations. The results contribute to broader discussions on pedagogical transformation in Islamic educational contexts, demonstrating how targeted innovations can drive academic achievement in under-resourced yet culturally rich learning environments.